PENGUATAN NORMA SYARAT DISPENSASI KAWIN DALAM UPAYA PENCEGAHAN PERKAWINAN ANAK BERDASARKAN PERSPEKTIF TEORI TUJUAN HUKUM - Sulistyarini (Penerbit Universitas Atma Jaya Yogyakarta, 2023)
Marriage dispensation is a form of exception to marriages performed below the minimum age limit stipulated by law, which is 19 years. This arrangement results in the stipulation of the minimum age limit for marriage being deviated, exacerbated by the ambiguity of the norms of requirements in the application for a marriage dispensation, resulting in applications for a marriage dispensation that are often granted without being based on urgent reasons that show the urgency of the implementation of marriage for children who have not reached the age limit for marriage. This paper will examine strengthening the norms of marriage dispensation requirements as an effort to prevent child marriage by using the theory of legal purposes. This research is a normative legal research using statutory and case approaches. The results of this research conclude that the normative requirements contained in the provisions of Article 7 Paragraph (2) of Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage are not accompanied by clear boundaries as standardization for judges in deciding requests for dispensation married for various reasons, resulting in judges interpreting the meaning of the article broadly so that the granting of a marriage dispensation request is highly dependent on the subjectivity of judges. This reduces the spirit of preventing child marriage and does not manifest the values ​​of justice, benefit, and legal certainty.